BENJAMIN WONG DOES COUNTRY PROUD, EMERGES AMONG TOP TEN PARTICIPANTS AT IBB 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 5 July 2016 A student from SMK Methodist, Sibu, Sarawak, Benjamin Wong Yi Ren, 16, did the country proud by emerging among the top ten participants at the International Brain Bee (IBB) Championship 2016 competition held in Copenhagen, Denmark on 30 June to 4 July 2016.